Synthesis of Phenyl-1,3-thiazole Substituted Amino s-triazines as Antibacterial Agents - Gahtori, Prashant; Singh, BK; Das, Aparoop (Dhaka University Journal of Pharmaceutical Sciences, 2009)
Amino s-triazines are widely believed to exert their antibacterial effects by nonspecific mechanisms. We assessed the extent to which physicochemical properties can be exploited to promote discriminative activity. In a wide search program towards new and efficient antibacterial agents, a series of amino substituted s-triazines were synthesized and subsequently screened for their in-vitro antibacterial activity against three Gram positive (Bacillus subtilis, B. cereus, Staphylococcus aureus) and three Gram-negative microorganism (Salmonella typhi, Escherichia coli, Klebsiella aerogenes) by the broth dilution technique, recommended by European Committee for antimicrobial susceptibility testing (EUCAST) with reference to streptomycin. The phenyl-1,3-thiazole substituted amino-s-triazine derivatives showed good antibacterial activity. Key words: Antibacterial activity, Bacterial resistance, Broth dilution technique, Physicochemical properties, s-Triazine. doi: 10.3329/dujps.v7i2.2164 Dhaka Univ. J. Pharm. Sci. 7(2): 107-111, 2008 (December)